Use of chitosan for the control of postharvest anthracnose and quality in avocados - Marques, K. M. [UNESP]; Galati, V. C. [UNESP]; Fernandes, J. D.R. [UNESP]; Guimarães, J. E.R. [UNESP]; Silva, J. P. [UNESP]; Mattiuz, B. H. [UNESP]; Mattiuz, C. F.M. (International Society for Horticultural Science (ISHS), 2016)
The aim of this work was to evaluate the antifungal potential of chitosan for the control of postharvest anthracnose in 'Breda' avocado fruit. For in vitro assessment, chitosan was incorporated into a melting PDA culture medium to obtain desired concentrations (0; 0.25; 0.50; 1.0; 1.5 and 2.0%), with six replications. For in vivo testing, fruits were infected with 25 μL C. gloeosporioides conidial suspension, and stored for 10 h at 22°C. The infected fruits were immersed for 1 min in a chitosan solution at above concentrations. After, the fruits were stored for seven days at 22±2°C and 80±3% relative humidity (RH). The experiment was performed in a totally randomized design, factorial scheme, four replications with five fruits each. To analyze the variance of the data, an F test was conducted, and the average values of each variable were compared with the Tukey test (P≤0.05). The concentration from 1.0% chitosan inhibited fungal growth and conidia germination in vitro of C. gloeosporioides. Chitosan application to fruit at 1.0% provided lower disease severity and incidence, reduced activity of phenylalanine ammonia lyase, peroxidase, and polyphenol oxidase enzymes. In addition, chitosan decreased respiratory rate, ethylene production, and fresh mass loss; however, increased pulp firmness. In conclusion, we would infer that 1.0% of chitosan is a potential natural covering for avocados 'Breda' during postharvest storage due to its fungicidal action against anthracnose and fruit quality maintenance.
Keywords: Colletotrichum gloeosporioides; Diseases; Enzymes; Natural product; Persea americana